Aryl‐Aryl Cross‐Coupling with Hypervalent Iodine Reagents: Aryl Group Transfer Reactions. Issue 43 (18th November 2020) - Ghosh, Manoj Kumar; Rout, Nilendri
Abstract: Aryl‐aryl cross‐coupling are a unique class of C−C bond formation reaction in organic chemistry. From last few years, various synthetic methods have been developed for aryl‐aryl cross‐coupling reaction using hypervalent iodine (III) reagents as an aryl group donor. This review highlights exciting synthetic protocols that have been used for aryl‐aryl cross‐coupling reactions with hypervalent iodine reagents employing aryl group transfer reaction. The review has categorized the metal‐catalyzed and metal free aryl‐aryl cross‐coupling reactions separately using hypervalent iodine reagents. Also this review provides the mechanistic prospective involves for aryl‐group transfer reaction. Abstract : This review has provided the recent advancement in the field of aryl‐aryl corss‐coupling reactions employing aryl group transfer reaction from hypervalent iodine reagents. Biaryls are synthetically important structural motifs as buillding blocks and also useful as a ligand in asymmetric organocatalysis. Due to huge demand biaryl synthesis always gained a considerable attention. This review separetely described the metal‐catalyzed aryl‐aryl cross‐coupling reactions and the metal‐free aryl‐aryl cross‐coupling reactions using hypervalent iodine reagents as an aryl donor in last 20 years.